TRICKY VEGGIES: FRUIT AND VEGETABLES IN FRENCH AND CROATIAN PHRASES (PALIMPSEST / ПАЛИМПСЕСТ, 2017)
This paper deals with a picturesque element in the topics represented by phrases i.e. phrasemes, one part of which is a fruit or vegetable name. Starting from French, where this type of phrases is rather common, we will base our remarks on a corpus comprising a hundred phrasemes, which will first be described from a linguistic perspective. Taking the premise that (1) linguistic signs are imposed by language as a social code and are therefore fixed and (2) signs consciously used to comminicate are intentional signs, we will study the way in which desemantisation takes place and propose a typology based on our observations. Then we will look for the equivalents in Croatian, the language in which the names of fruit and vegetables are not very much used in phrasemes. Using Umberto Eco's approach that translation is negotiations, we propose a range of strategies, from a literal translation to equivalence, realised with an existing Croatian phrase or through adjustments: adaptation, transposition, and banalisation. We will explore possible strategies that are to be used and attempt to determine the relevance of the proposed solutions.